К вопросу о питании бычка-пуголовки звездчатой — Веnthophilus stellatus (Gobiidae) — Днестровского лимана - Страутман, И.Ф. (Вестник зоологии, 1976)
Qualitative and quantitative composition of food was analyzed in 215 individuals of Benthophilus stellatus (S a u v a g e) from the Dniester estuary. Changes in food spectra are determined depending on the season of a year, sex and dimensions of gobies. Food relations of Benthophilus stellatus and other species of gobies from the Dniester estuary are traced.